Application of transposition procedure to the translation of emotive words in Krsna text - Suryasa, I Wayan; Sudipa, I Nengah; Puspani, Ida Ayu Made; Netra, I Made (e-Journal of Linguistics, 2019)
The current study is aimed at investigating the application of the transposition procedure to the translation of the emotive words found in Krsna text. The emotive words used are based on the cognitive  scenario. There are five emotive words described. They are happy, sad, fear, anger, envious, and ashamed . The transposition procedure was appplied to the replacement of one word class by another. There is no change in meaning. The transportation procedure can be applied intralinguistically, referring to as particular language. The original expression is the base one and the result is the transposed expression . The highly versatile translation procedure is transposition. The stylistic value of the transposed expression is sometimes substantially different from the base expression. Transposition can render the nuance of style, and used as a main means of finetuning  the stylistic elegance of the translation product.